Approaches for modelling interstitial ultrasound ablation of tumours within or adjacent to bone: Theoretical and experimental evaluations. (November 2013) - Scott, Serena J.; Prakash, Punit; Salgaonkar, Vasant; Jones, Peter D.; Cam, Richard N.; Han, Misung; Rieke, Viola; Burdette, E. Clif; Diederich, Chris J.
Abstract Purpose: The objectives of this study were to develop numerical models of interstitial ultrasound ablation of tumours within or adjacent to bone, to evaluate model performance through theoretical analysis, and to validate the models and approximations used through comparison to experiments. Methods: 3D transient biothermal and acoustic finite element models were developed, employing four approximations of 7-MHz ultrasound propagation at bone/soft tissue interfaces. The various approximations considered or excluded reflection, refraction, angle-dependence of transmission coefficients, shear mode conversion, and volumetric heat deposition. Simulations were performed for parametric and comparative studies. Experiments within ex vivo tissues and phantoms were performed to validate the models by comparison to simulations. Temperature measurements were conducted using needle thermocouples or magnetic resonance temperature imaging (MRTI). Finite element models representing heterogeneous tissue geometries were created based on segmented MR images. Results: High ultrasound absorption at bone/soft tissue interfaces increased the volumes of target tissue that could be ablated. Models using simplified approximations produced temperature profiles closely matching both more comprehensive models and experimental results, with good agreement between 3D calculations and MRTI. The correlation coefficients between simulated and measured temperature profiles in phantoms ranged from 0.852 to 0.967 (p-value < 0.01) for the four models. Conclusions: Models using approximations of interstitial ultrasound energy deposition around bone/soft tissue interfaces produced temperature distributions in close agreement with comprehensive simulations and experimental measurements. These models may be applied to accurately predict temperatures produced by interstitial ultrasound ablation of tumours near and within bone, with applications toward treatment planning.